Approaches to Evaluate Lung Inflammation in Translational Research. Issue 1 (January 2018) - Meyerholz, David K.; Sieren, Jessica C.; Beck, Amanda P.; Flaherty, Heather A.
Inflammation is a common feature in several types of lung disease and is a frequent end point to validate lung disease models, evaluate genetic or environmental impact on disease severity, or test the efficacy of new therapies. Questions relevant to a study should be defined during experimental design and techniques selected to specifically address these scientific queries. In this review, the authors focus primarily on the breadth of techniques to evaluate lung inflammation that have both clinical and preclinical applications. Stratification of approaches to assess lung inflammation can diminish weaknesses inherent to each technique, provide data validation, and increase the reproducibility of a study. Specialized techniques (eg, imaging, pathology) often require experienced personnel to collect, evaluate, and interpret the data; these experts should be active contributors to the research team through reporting of the data. Scoring of tissue lesions is a useful method to transform observational pathologic data into semiquantitative or quantitative data for statistical analysis and enhanced rigor. Each technique to evaluate lung inflammation has advantages and limitations; understanding these parameters can help identify approaches that best complement one another to increase the rigor and translational significance of data.